2020
DOI: 10.3847/1538-4357/ab621f
|View full text |Cite
|
Sign up to set email alerts
|

Continuum Enhancements, Line Profiles, and Magnetic Field Evolution during Consecutive Flares

Abstract: During solar flares, magnetic energy can be converted into electromagnetic radiation from radio waves to γ rays. Enhancements in the continuum at visible wavelengths give rise to white-light flares, as well as continuum enhancements in the FUV and NUV passbands. In addition, the strong energy release in these events can lead to the rearrangement of the magnetic field at the photospheric level, causing morphological changes in large and stable magnetic structures like sunspots. In this context, we describe obse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 97 publications
(89 reference statements)
0
6
0
Order By: Relevance
“…IRIS observes substructures moving bi-directionally along the flare ribbons in a couple of events, indicating that reconnection in the quasi-separatrix layer between two flux systems has caused slip-running reconnection to occur (Li et al, 2018b(Li et al, , 2019b. A fan-spine topology was identified in another event using IRIS 2796 Å SJI observations, and because of this topology, slip-running reconnection is identified as a possible trigger mechanism (Zuccarello et al, 2020).…”
Section: Initiation Of Coronal Mass Ejections and Flaresmentioning
confidence: 93%
“…IRIS observes substructures moving bi-directionally along the flare ribbons in a couple of events, indicating that reconnection in the quasi-separatrix layer between two flux systems has caused slip-running reconnection to occur (Li et al, 2018b(Li et al, , 2019b. A fan-spine topology was identified in another event using IRIS 2796 Å SJI observations, and because of this topology, slip-running reconnection is identified as a possible trigger mechanism (Zuccarello et al, 2020).…”
Section: Initiation Of Coronal Mass Ejections and Flaresmentioning
confidence: 93%
“…The HMI continuum intensity measurements are well known to produce artifacts when fast phenomena occur, such as flares (e.g., Martínez Oliveros et al 2014). Different processes such as mass motions, gradients in temperature and the magnetic field and in some cases lines in emission might produce complex signatures in the spectral lines (e.g., Mauas 1990;Zuccarello et al 2020). For example, Švanda et al (2018) studied the intensity of the 6 HMI passbands and the derived continuum emission during a large flare and compared it to Hinode/SP spectra and simulated HMI spectra where the iron lines were in emission.…”
Section: Possible Sources Of Error and Reliability Of Hmi's Data Duri...mentioning
confidence: 99%
“…Wang et al (1994) showed impulsive magnetic shear enhancements along the flaring neutral line during six X-class flares, and Wang et al (2012) observed the rapid enhancement of magnetic shear in the localized region of the PIL during an X2.2 flare that occurred in NOAA 11158. This is mostly caused by the changes in the photospheric magnetic fields, especially the enhancement of horizontal magnetic fields near the PIL region (Wang et al 2012;Zuccarello et al 2020;Vasantharaju et al 2022), as a consequence of coronal implosion during flares (Hudson et al 2008). However, the result could be different if the analysis is extended from localized regions of the PIL to the whole flaring area.…”
Section: Magnetic Nonpotentiality and Confinednessmentioning
confidence: 99%